(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aimed to examine the effect of varied underhand passing exercises on improving forearm passing skills in volleyball extracurricular students at SMA Negeri 8 Palembang. The research was guided by the hypothesis that training variations would significantly enhance students’ forearm passing performance. A pre-experimental design using a one-group pretest–posttest approach was employed, involving 20 male students aged 14–16 years selected through purposive sampling. The study was conducted in Palembang, South Sumatra, and data were collected using a forearm passing test in which participants performed continuous wall passes for one minute. Data analysis was carried out using SPSS version 26, including normality and homogeneity tests, followed by a paired sample t-test. The findings showed a significant performance improvement, with the mean score increasing from 23.75 in the pretest to 27.35 in the posttest. Statistical analysis revealed t(19) = 7.532, p < 0.05, confirming the effectiveness.